Building Software, Building Community: Lessons from the rOpenSci Project. Issue 1 (16th November 2015) - Boettiger, Carl; Chamberlain, Scott; Hart, Edmund; Ram, Karthik
ROpenSci is a developer collective originally formed in 2011 by graduate students and post-docs from ecology and evolutionary biology to collaborate on building software tools to facilitate a more open and synthetic approach in the face of transformative rise of large and heterogeneous data. Born on the internet (the collective only began through chance discussions over social media), we have grown into a widely recognized effort that supports an ecosystem of some 45 software packages, engages scores of collaborators, has taught dozens of workshops around the world, and has secured over 480, 000 in grant support. As young scientists working in an academic context largely without direct support for our efforts, we have first hand experience with most of the the technical and social challenges WSSSPE seeks to address. In this paper we provide an experience report which describes our approach and success in building an effective and diverse community.